Peculiarities of doping of nanograined thermoelectric TiNiSn by 3d noble and transition metals. (July 2018) - Kirievsky, K.; Orr, Y.; O'Neill, A.; Fuks, D.; Gelbstein, Y.
Abstract: The effect of nano-structures and in particular nano-grains on reduction of the lattice thermal conductivity, via enhanced phonon scattering, and thereby increasing of the thermoelectric figure of merit, is well established. Nevertheless, the effect of grain boundaries on the electronic transport properties of nano-grained thermoelectric materials, was rarely considered. Such an electronic contribution of the grain boundaries might significantly affect the thermoelectric efficiency of such materials. In the current research this effect is theoretically studied by the density functional theory approach, for the thermoelectrically promising half-Heusler TiNiSn compound, upon a simultaneous introduction of grain-boundaries and either Fe or Cu doping. It is shown that the combined donor effect of grain boundaries with the Cu donor nature and Fe acceptor nature exhibits interesting peculiarities that should be considered upon synthesis of related polycrystalline materials. For the case of Cu doping, an enhanced n -type conductivity was attributed to the interaction between the totally occupied 3 d -shell of Cu and grain-boundary states, while upon Fe doping, grain-boundary states interaction with the partly occupied 3 d -states of electrons in Fe, might vanish the energy gap completely, creating a semi-metal. Based on these case studies, a general route for enhancing of the thermoelectric potential of chemically doped nano-grained thermoelectric materials is proposed. Highlights: The effect of nano-structures and in particular nano-grains on reduction of the lattice thermal conductivity, via enhanced phonon scattering, and thereby increasing of the thermoelectric figure of merit, is well established. Nevertheless, the effect of grain boundaries on the electronic transport properties of nano-grained thermoelectric materials, was rarely considered. Such an electronic contribution of the grain boundaries might significantly affect the thermoelectric efficiency of such materials. In the current research this effect is theoretically studied by the density functional theory approach, for the thermoelectrically promising half-Heusler TiNiSn compound, upon a simultaneous introduction of grain-boundaries and either Fe or Cu doping. It is shown that the combined donor effect of grain boundaries with the Cu donor nature and Fe acceptor nature exhibits interesting peculiarities that should be considered upon synthesis of related polycrystalline materials. For the case of Cu doping, an enhanced n -type conductivity was attributed to the interaction between the totally occupied 3 d -shell of Cu and grain-boundary states, while upon Fe doping, grain-boundary states interaction with the partly occupied 3 d -states of electrons in Fe, might vanish the energy gap completely, creating a semi-metal. Based on these case studies, a general route for enhancing of the thermoelectric potential of chemically doped nano-grained thermoelectric materials is proposed.